Pendekatan STEM dalam Metode Pengajaran dengan Topik Gravitasi pada Santri di Pondok Pesantren - Muhammad Syafiq Ashfa Hubbi; Desmaliza Desmaliza; Dewi Indrawati; M. Mualif; Eva Nurfaidah; Muhammad Kafnun Kafi (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2026)
This study discusses the implementation of the STEM (Science, Technology, Engineering, and Mathematics) approach in teaching the topic of gravity to students in Islamic boarding schools (pesantren). In addition to mastering religious knowledge, 21st-century learners are expected to develop critical thinking skills, problem-solving abilities, technological literacy, creativity, and adaptability to scientific and technological advancements. The integration of STEM into science learning in pesantren is expected not only to strengthen students’ conceptual understanding of gravity but also to connect scientific phenomena with Islamic values and perspectives. This article highlights the role of STEM in improving the quality of learning, strategies for integrating Islamic values into science education, and the relevance of STEM implementation within the pesantren context. The findings indicate that the STEM approach is capable of creating contextual, applicative, and meaningful learning experiences by encouraging students to actively explore concepts through observation, analysis, and problem-solving activities. Furthermore, STEM-based learning supports the development of scientific understanding while reinforcing religious values. Therefore, the implementation of STEM in pesantren contributes to fostering students who are intelligent, adaptive, technologically literate, and firmly grounded in Islamic values in facing contemporary educational challenges.